A Török Birodalom megítélésének változásai a magyar földrajzi-államismereti irodalomban a XIX. századtól a felbomlásáig - Hajdú, Zoltán (Közép-Európai Közlemények, 2014)
The Hungarian–Turkish connections were rearranged basically many times from the 1300’s to 19th Century. In the early 19th Century the Turkish Empire turned to be a key figure in the scientific analyses in the Hungarian Geography and Statistics. The old position of Turkish Empire as “enemy” turned to be “friend” for the middle of the 19th Century. The Hungarian geographical and statistical researches were based on Turkish and Western European sources. The Hungarian researches tried to be correct and deep in understanding the Turkish inner structures and international connections. Between 1878 and 1914 problems of Turkey were in the focuse of the Hungarian scientific and political thinking. In 1916 during the World War a state founded scientific research institute was established in Istambul.